Adaptive variation in size of tropical soft bottom benthic megafauna related to biotic and abiotic factors - Gómez, Luis Alfonso (2017)
Understanding and predicting adaptations in body size of megabenthic invertebrates remains a major challenge in marine macroecology. This study was conducted in order to investigate size variations of benthic megafauna in the tropics and to identify the effect of biotic and abiotic factors that may produce changes to these organisms, testing unresolved hypothesis and paradigms of deep sea ecology from subtropical and temperate areas. The study area covered the continental shelf of the Colombian Caribbean. The samples were collected during 1998, 2001 and 2005, using semi-globe demersal net for a water depth of 10 to 500 m. The most common species were selected for further study: Eudolium crosseanum, Cosmioconcha nitens, Nuculana acuta (mollusks), Astropecten alligator, Brissopsis atlantica, B. elongata (equinoderms), Anasimus latus, Chasmocarcinus cylindricus and Achelous spinicarpus (crustaceans). Generalized Additive Models were used to detect significant changes in size and to infer the effects of biotic and environmental factors on organisms’ size. The dependent variable was size and the predicting model variables were depth, temperature, intraspecific density, interspecific density, richness, latitude, and longitude. A total of 7 000 individuals were measured. Six species showed an increase in body size towards deeper and colder sites. These species inhabit shallow and deep environments that exceed a variation in temperature of 10 °C. There was a remarkable size reduction in areas affected by the Magdalena River, possibly due to major physicochemical changes caused by the river. This region has the lowest planktonic primary productivity within the study area. An increase in sizes was observed north of the Magdalena River (long 74°W - 71°W & lat of 11°N - 13°N), which may be attributable to the coastal upwelling occurring in this part of Colombia. The relationship between the density of benthic organisms and size was not clear. However, five species showed an inverse relation with intraspecific density and three with interspecific density. Temperature and depth were the variables that best explained the variations in size. Most of the studied species showed an increase in body size when temperature dropped along the bathymetric range. The trend of increasing size in deeper zones is contrary to the prediction of the optimal size theoretical model (but consistent with recent studies), which indicates a reduction in organisms’ size in the deep sea, due to food limitation with increasing depth. It is possible that this increase in size is an adaptation to maximize energy, which is frequently observed in the coldest habitats of several species. Future studies in Caribbean should examine variations in size of benthic megafauna towards deeper zones (more than 500 m), were temperature is less variable and then other factors can play a more important role determining the size of these organisms.